Qualitative study on handling mental health issues in Serbian schools: Non-navigation plane which luckily often lands well: English - Radanovic, Ana; Kovacevic Lepojevic, Marina; Micic, Isidora; Trajkovic, Marija (Psihološka istraživanja, 2026)
Compared to developed countries, Serbia’s educational system is less responsive to students’ mental health needs, with limited formal guidance available for addressing mental health issues in schools. The present study examined how school staff in various professional roles respond to students with mental health issues. We analyzed responses to an open-ended question completed by 830 school staff members from primary and secondary schools in Serbia using qualitative content analysis. Participants were asked to describe their most recent response to noticing or being informed that a student was experiencing mental health difficulties. The results revealed internally developed practices that vary across staff roles, yet certain patterns consistently emerged. Two primary strategies were observed: conversations and referrals. Staff generally initiate their response by gathering information through brief, often protocol-driven, discussions, which may convey to students a sense of limited care. Referrals to external experts or institutions were common across all roles, reflecting the need for support outside the school due to a lack of sufficient inschool professionals. Teachers also reported collaborating with external specialists, highlighting best practices constrained by unequal service availability across regions. These findings contribute to a broader understanding of school-based mental health practices, particularly in educational systems that are less responsive to students’mental health needs, as well as in societies facing multiple crises.